Ismailism and Islam in modern South Asia community and identity in the age of religious internationals - Mukherjee, Soumen (Cambridge, United Kingdom Cambridge University Press, 2017)
"Explores the evolution of a Shia Ismaili identity in modern South Asia and traces the genealogies of conceptual categories and institutions that conditioned the historical process" --Provided by publisher.
The Khoja Ismailis and legal polemics: religion and customs in nineteenth century Bombay -- The Howardian moment: morality, Aryanism, and scholarship -- Pan-Islamism and an Asiatic spirit: postnational subjectivities in an age of 'transition' -- The Hazir Imam, Ismailism, and Islam in late colonial South Asia -- The importance of being Ismaili: religious normativity and the Ismaili International in the age of global assemblages.
Includes bibliographical references (pages 181-198) and index.
Keywords: Ismailites -- South Asia; Shīʻah -- South Asia; Shiites -- South Asia